Remembrance of Jews in contemporary catholic homilies - Makuchowska, Marzena (Stylistyka, 2020)
The paper discusses the problem of transferring the memory of Jews through Polish contemporary Catholic homilies. In the biblical pericopies read throughout the liturgical year during Catholic mass, generally Jews play a negative role – as persecutors and killers of Jesus. According to the provisions of the Second Vatican Council, anti-Jewish content cannot be proclaimed in the Catholic Church, and the Bible, which according to the doctrine must remain unchanged, should be adequately commented on in homilies. The paper – on the example of about 40 homilies – shows, however, that priests who preach homilies do not use modern exegetic knowledge, but replicate stereotypes deeply rooted in culture, thus reproducing the centuries-old myth of the Jews as killers of God.